Fachtextsorten in arbeitsmarktorientierten Studienfächern vor dem Hintergrund der Entwicklung des polnischen Outsourcing-Sektors - Makowski, Jacek (Studia Germanica Posnaniensia, 2019)
This paper’s main goal is to present the outcome of a field study from 2015 among the companies representing the sector of modern services for business in the area of Lodz. The main interest of the study were the information on the foreign languages and languages for specific purposes being in use in the outsourcing sector on the local job market as well as the main areas of use of foreign languages. As a conclusion, the paper presents various examples of study and training exercises for the use of the German language in business communication.